2023
DOI: 10.3390/coatings13040686
|View full text |Cite
|
Sign up to set email alerts
|

A Wind Tunnel Test of the Anti-Icing Properties of MoS2/ZnO Hydrophobic Nano-Coatings for Wind Turbine Blades

Abstract: Wind turbines operating in cold regions are prone to blade icing, which seriously affects their aerodynamic characteristics and safety performance. Coatings are one of the effective solutions to the icing problem on wind turbine blades. In this study, MoS2/ZnO/PDMS superhydrophobic nano-anti-icing coatings were prepared using the hydrothermal method and the liquid phase method. SEM revealed that the MoS2/ZnO coating was a typical superhydrophobic nanostructure with an ultra-thin sheet-like morphology of cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The Scanning Electron Microscope (SEM) image of a porous superhydrophobic PVDF coating is shown in Figure 34 [104]. A superhydrophobic nano anti-icing coating of MoS2/ZnO/PDMS (polydimethylsiloxane) was prepared by hydrothermal method and liquid phase method [105]. This material has ultra-thin sheet cluster morphology and hilly nano-rough structure, and the CA and SA with water droplets are 152.1° and 4.7°, respectively.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The Scanning Electron Microscope (SEM) image of a porous superhydrophobic PVDF coating is shown in Figure 34 [104]. A superhydrophobic nano anti-icing coating of MoS2/ZnO/PDMS (polydimethylsiloxane) was prepared by hydrothermal method and liquid phase method [105]. This material has ultra-thin sheet cluster morphology and hilly nano-rough structure, and the CA and SA with water droplets are 152.1° and 4.7°, respectively.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Thermal coating mainly uses the photothermal or electrothermal of the coating to heat the icing on the surface until melts. Liu et al [106] proposed a robust amphibious coating system consisting of Fluorinated Multi-Wall Carbon Nano Tubes (FMWCNT) and commercial polyurethane, including a photothermal layer (P), a thermal conductive layer (C) and a A superhydrophobic nano anti-icing coating of MoS 2 /ZnO/PDMS (polydimethylsiloxane) was prepared by hydrothermal method and liquid phase method [105]. This material has ultra-thin sheet cluster morphology and hilly nano-rough structure, and the CA and SA with water droplets are 152.1 • and 4.7 • , respectively.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Feng et al reported that a MoS 2 /ZnO/PDMS superhydrophobic nanoanti-icing coating could effectively inhibit the icing of wind turbine blades. The rough porous surface could be in contact with the liquid to form an air cushion, reducing the adhesion between the ice and the surface coating, thereby effectively inhibiting icing . Furthermore, the morphology of MoS 2 nanomaterials is notably diverse, including nanoflowers (FLs), nanowires, nanorods, microspheres, and nanosheets. , Due to the different surface properties of these morphologies, there are differences in their ice control and photothermal performance.…”
Section: Introductionmentioning
confidence: 99%